PEMANFAATAN REFUGIA (Tagetes erecta L.) TERHADAP INTENSITAS SERANGAN HAMA LALAT BUAH (Bactrocera sp.) PADA TANAMAN TERUNG (Solanum melongena) DAN BERAT BUAH SEBAGAI SUMBER BELAJAR BIOLOGI BERUPA BUKLET - Anisau Sholihah; Anak Agung Oka; Agus Sutanto (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
Fruit flies (Bactrocera sp.) are one of the main pests that cause serious damage to eggplant (Solanum melongena), resulting in a decrease in the quality and quantity of the harvest. The purpose of this study was to examine the use of marigold (Tagetes erecta L.) refugia in reducing the intensity of fruit fly (Bactrocera sp.) attacks on eggplant plants. The research method used was a field experiment consisting of 2 fields, namely land with refugia and land without refugia. The parameters observed included the level of fruit fly attack intensity, weight and number of eggplant fruits. Data will be analyzed statistically to determine the effect of treatment on the observed variables. The findings of this study indicate that planting (Tagetes erecta L.) as a refugia significantly reduces the level of fruit fly (Bactrocera sp.) attacks on eggplant plants. The results of this study indicate that there are benefits of refugia plants on the intensity of fruit fly pest attacks on eggplant fruit. It is known that the analysis of the highest fruit attack intensity is in land without refugia with an average value of 60%, which is included in the severe category. The t-test results yielded a calculated t-value of 4.39 and a calculated t-value of 2.009. Fruit weight showed a calculated t-value of 11.46 and a t-value of 1.68. The results of this study were then implemented in the development of a booklet as a biology learning resource, specifically for sub-ecosystem material on interactions occurring within ecosystems for grade 10 high school students.